2010
DOI: 10.1016/j.cognition.2010.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Gaze allocation in a dynamic situation: Effects of social status and speaking

Abstract: a b s t r a c tHuman visual attention operates in a context that is complex, social and dynamic. To explore this, we recorded people taking part in a group decision-making task and then showed video clips of these situations to new participants while tracking their eye movements. Observers spent the majority of time looking at the people in the videos, and in particular at their eyes and faces. The social status of the people in the clips had been rated by their peers in the group task, and this status hierarc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
223
1
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 239 publications
(246 citation statements)
references
References 60 publications
20
223
1
2
Order By: Relevance
“…This theory predicts that a very different result might be obtained if participants could camouflage their looking behavior (e.g., by wearing sunglasses). Finally, although we have shown that participants look less at live versus videotaped others, it is likely that variations of the present study, such as using two well-acquainted participants or introducing social-status discrepancies (19) between participants could have powerful mediating influences on observed behavior.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This theory predicts that a very different result might be obtained if participants could camouflage their looking behavior (e.g., by wearing sunglasses). Finally, although we have shown that participants look less at live versus videotaped others, it is likely that variations of the present study, such as using two well-acquainted participants or introducing social-status discrepancies (19) between participants could have powerful mediating influences on observed behavior.…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Kuhn et al (18) in which participants watched a video of a magic trick, the proportion of fixations on the head and eyes was nearly 70%. Likewise, when participants were asked to watch videos of other students engaging in conversation, 77% of fixations were directed to the people in the clips (19).…”
mentioning
confidence: 99%
“…, too, found that their observers looked at the next speaker only after he or she had already begun to speak. One possible reason for this, they state, could be that participants in other studies (e.g., Foulsham et al, 2010) may have been more eager to see the reactions of the participants due to the decision task they were asked to complete. They argue that the gaze behavior of their participants merely observing dialogs may have been "less tightly linked to the turn-taking than if the task would have been more engaging, or if the subjects would have actually taken part in the conversation" (Hirvenkari et al, 2013, p. 6).…”
Section: Third-person Perspective Eye-tracking Studies On Turn-takingmentioning
confidence: 90%
“…With the exception of some studies (Foulsham et al, 2010;Edlund et al, 2012;, the stimuli in third-person perspective eye-tracking studies were scripted and strongly controlled, which has a range of implications. For one thing, it means that the dialogs were presumably fairly carefully spoken and had rather long gaps between turns and few if any overlaps.…”
Section: Methodological Considerationsmentioning
confidence: 99%
See 1 more Smart Citation